Teaching media literacy, did we forget literacy? - Pylkkö, Leena; Pylkkö, Pauli (Qualitative and Quantitative Methods in Libraries; Vol 6 No 1 (2017): March 2017 Issue, 2019)
This paper gives an overall philosophical framework, based on Nelson Goodman’s semiotics, to describe work in library pedagogy including new media literacy. According to this view, knowledge is literacy, in other words, ability to recognize and use the rules of different symbol-systems in order to ”make worlds”. This view on information search is broader than described in Carol Kuhlthau’s well-known description of the Information Search Process. Some practical examples from library pedagogy in Turku City Library are reviewed, together with findings that show that new information technology hasn’t enhanced school performance as much as maybe was expected. These findings fit the overall philosophical view on literacy as worldmaking. The authors suggest that a semiotic-philosophical view on what thinking is helps us to challenge hasty and immature digitization.